The Mergers & acquisitions handbook - Rock, Milton L. (New York : McGraw-Hill, 1987)
Includes articles by more than 60 of the leading M&A practitioners, plus principles and techniques illustrated with "Fortune 500" case studies. This title also includes the restructuring of debt-laden corporations, issues impacting medium-sized companies, and the implications of global markets.
Includes index.
oif 10/10/14
Loan
Keywords: Consolidation and merger of corporations -- United States -- Handbooks, manuals, etc